Biologic activities of recombinant human-beta-defensin-4 toward cultured human cancer cells - Gerashchenko, O.L.; Zhuravel, E.V.; Skachkova, O.V.; Khranovska, N.N.; Filonenko, V.V.; Pogrebnoy, P.V.; Soldatkina, M.A. (Experimental Oncology, 2013)
Aim - the aim of the study was in vitro analysis of biological activity of recombinant human beta-defensin-4 (rec-hBD-4). Methods: hBD-4 cDNA was cloned into pGEX-2T vector, and recombinant plasmid was transformed into E. coli BL21(DE3) cells. To purify soluble fusion GST-hBD-4 protein, affinity chromatography was applied. Rec-hBD-4 was cleaved from the fusion protein with thrombin, and purified by reverse phase chromatography on Sep-Pack C18. Effects of rec-hBD-4 on proliferation, viability, cell cycle distribution, substrate-independent growth, and mobility of cultured human cancer cells of A431, A549, and TPC-1 lines were analyzed by direct cell counting technique, MTT assay, flow cytofluorometry, colony forming assay in semi-soft medium, and wound healing assay. Rech-BD-4 was expressed in bacterial cells as GST-hBD-4 fusion protein, and purified by routine 3-step procedure (affine chromatography on glutathione-agarose, cleavage of fusion protein by thrombin, and reverse phase chromatography). Analysis of in vitro activity of rec-hBD-4 toward three human cancer cell lines has demonstrated that the defensin is capable to affect cell behaviour in concentration-dependent manner. In 1 - 100 nM concentrations rec-hBD-4 significantly stimulates cancer cell proliferation and viability, and promotes cell cycle progression through G2/M checkpoint, greatly enhances colony-forming activity and mobility of the cells. Treatment of the cells with 500 nM of rec-hBD-4 resulted in opposite effects: significant suppression of cell proliferation and viability, blockage of cell cycle in G1/S checkpoint, significant inhibition of cell migration and colony forming activity.